Extraction d’ADN à partir d’oignon (Allium fistulosum): différentes méthodes de révélations. - CHAREF, AISSA Fatima Zohra; OGAL, Salima (My University, 2024)
In our work, we isolated DNA from white onion (Allium fistulosum L.), then subjected the DNA jellyfish to macroscopic and microscopic observations with and without methyl green staining. The results of the microscopic observations were very conclusive, as we were able to observe DNA fibres. We then quantified the DNA and assessed its degree of purity in solution by taking ultraviolet spectrophotometer readings at wavelengths of 260 nm and 280 nm. The results obtained were 38.2 μg/ml for the quantity of DNA and 0.93 for the purity ratio, which indicates that the quantity of DNA is fairly small in our solutions and that we have a high level of protein contamination. The DNA jellyfish were preserved in 96% ethanol and then dried and kept as is.
Keywords: DNA extraction; onion; cell lysis; grinding; methyl green